Can Tort Law be used to deflect the impact of criminal sanctions? The role of the illegality defence - Goudkamp, J (LexisNexis, 2006)
The suggestion that persons convicted of criminal offences could obtain compensation or indemnity in tort in respect of penalties imposed by the criminal law would undoubtedly strike most people as bizarre and abhorrent. However, in recent years, an increasing number of actions have been brought seeking to do just this. While these actions have generally been unsuccessful as a result of the application of the illegality defence, the courts have failed to properly articulate the public policy considerations which support and militate against the invocation of this defence in this context. This article explores these considerations and concludes that sanction-shifting actions may be permissible in limited circumstances.